Cover Feature: SnCN2: A Carbodiimide with an Innovative Approach for Energy Storage Systems and Phosphors in Modern LED Technology (ChemElectroChem 22/2020). Issue 22 (21st October 2020) - Braun, Cordula; Mereacre, Liuda; Hua, Weibo; Stürzer, Tobias; Ponomarev, Ilia; Kroll, Peter; Slabon, Adam; Chen, Zheng; Damour, Yann; Rocquefelte, Xavier; Halet, Jean‐François; Indris, Sylvio
Abstract : The Cover Feature illustrates that SnCN2 is a multifunctional material that can be used as a luminescent phosphor when doped with Eu/Tb, or as an electrode material for Li‐ion batteries when doped with transition metals. More information can be found in the Article by C. Braun et al .